Vitamin B1 as a scavenger of reactive oxygen species photogenerated by vitamin B2 - Natera, Jose Eduardo (2011)
Kinetics and mechanism of photoprocesses generated by visible light-irradiation of the system riboflavin (Rf, vitamin B2) plus Thiamine (Th) and Thiamine pyrophosphate (ThDP), representing vitamin B1, was studied in pH 7 water. A weak dark complex vitamin B2-vitamin B1, with a mean value of 4 ± 0.4 m-1 is formed. An intricate mechanism of competitive reactions operates upon photoirradiation, being the light only absorbed by Rf. Th and ThDP quench excited singlet and triplet states of Rf, with rate constants in the order of 109 and 106m-1s-1, respectively. With Vitamin B1 in a concentration similar to that of dissolved molecular oxygen in water, the quenching of triplet excited Rf by the latter is highly predominant, resulting in the generation of O2( 1Δg). Superoxide radical anion was not detected under work conditions. A relatively slow O2(1Δ g)-mediated photodegradation of Th and ThDP was observed. Nevertheless, Th and especially ThDP behave as efficient physical deactivators of O2(1Δg). The thiazol structure in vitamin B1 appears as a good scavenger of this reactive oxygen species. This characteristic, that presents at vitamin B1 as a potential photoprotector of biological entities against O2(1Δg) attack, was been experimentally confirmed employing the protein lisozime as a photo-oxidizable target.